Low level of the immune response against rabies virus in dogs and cats, a cross-sectional study in sheltered animals, Santander, Colombia - Trujillo-Rojas,Lina María (2018)
ABSTRACT: Rabies is an incurable and fatal progressive viral encephalomyelitis that causes approximately 61,000 deaths a year globally mainly by dog bites, which show the importance of anti-rabies vaccination in dogs to achieve elimination of the disease. In Colombia, multiple cases of human rabies transmitted by dogs and cats have been reported since 1999, showing an increased significance of cats in the transmission of rabies, mainly in rabies of wild origin. Therefore, the aim of the present study was to evaluate the development of neutralizing antibodies in dogs and cats during the mass vaccination campaign of the second half of 2015 in the city of Bucaramanga. For this purpose, a descriptive cross-sectional study with convenience sampling was conducted in 382 dogs and cats (295 dogs, 87 cats), and an evaluation of the humoral immune response of the animals was performed by quantitative ELISA. The prevalence of optimal neutralizing antibodies (>0.5 IU/ml) was only 32.76% (95% CI=28.05-37.46%) in the entire population studied and most of the animals did not have an adequate response to the vaccination, or seroconversion was not detected on them (65.45-95% confidence interval, CI=60.68-70.21%). Significant difference was found between the neutralizing antibody titers in cats and dogs, with a higher neutralizing response in cats. In conclusion, although mass vaccination campaigns for dogs and cats are the most important measure to interrupt virus circulation among the animals, achievement of a good neutralizing immune response in the animals is useful to demonstrate that vaccination has been successful, allowing the maintenance of the required minimum levels of population immunity. These results will allow the implementation of corrective measures in Bucaramanga to achieve better seroconversion rates. Other cities are expected to implement similar seroconversion assessments to verify the quality of effective anti-rabies vaccination in animal populations.